Herbal medicines, bio-diversity, and conservation strategies: proceedings of the national seminar, sponsored by All India Association for Christian Higher Education, New Delhi / (Acc. 3421) proceedings of the national seminar, sponsored by All India Association for Christian Higher Education, New Delhi - Rajak, R. C., 1943-; Rai, Mahendra; All India Association for Christian Higher Education (Dehra Dun, U.P., India : International Book Distributors, 1996)
Papers presented at the National Seminar on Herbal Medicines, Bio-diversity, and Conservation Strategies held at Chhindwara on February 26-27, 1994.
Keywords: Biodiversity conservation; Medicinal plants; Plant diversity conservation